THE PUBERTY EXPERIENCE OF ADOLESCENT FENOMENOLOGY STUDY IN PURWOKERTO - Endang Triyanto (Universitas Airlangga, 2017)
Introduction: Puberty as a period of transition from childhood to adulthood and the most difficult stages in human growth and development. Teenagers undergo during puberty will experience many physical and psychological changes that are very fast. The purpose was to explore experience of adolescents during their puberty. Method: Phenomenological method was used for data analysis. Participants are adolescents who are undergoing puberty in Purwokerto by purposive sampling. Data was collected by open ended depth interviews. Result: Researchers found four themes: changes in puberty, adolescent psychological problems, the perceived role of family and family behaviors that adolescents are expected to undergo during puberty. Adolescent girls experience menarche at age 12, while teenage boys have wet dreams at the age of 14 years. Discussion: Changes in the form of adolescent psychosexual fascination with the opposite sex and appearance. Adolescent social change seen with increasing activity with friends and peers. Researchers suggest the formation of peer counselor adolescents, clinical consultation and promotion of adolescent family development tasks.